What can we learn from the demise of the UkeU? : Evaluation of the lessons learnt - Conole, Gráinne; Carusi, Annamaria; de Laat, Maarten; Darby, Jonathan (Proceedings of the International Conference on Networked Learning, 2006)
This paper reports on an evaluation of the UkeU and the lessons which can be drawn from the experience. The study is based on two data sources: interviews and a study of documents. Semi-interviews interviews were undertaken with key stakeholders involved in the UKeU, including members of the learning technology team, representatives from SUN and the HEI partners. In particular we explore the relationship between the documented UkeU vision and how this was instantiated and its impact on practice. We will consider the way in which the UKeU was understood at its start-up (and even before), the aspirations it had with respect to the public/private partnership, and with respect to the roles and backgrounds it would need to bring together; and the acknowledgement of the difficulties it would face.